Republic of Mozambique : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2007)
The Fifth Review Under the Three-Year Arrangement under the Poverty Reduction and Growth Facility of the Republic of Mozambique explains macroeconomic performance. Growth has picked up, led by strength in the construction sector and a recovery in agricultural production. The strategy to consolidate macroeconomic stability in the context of scaling-up of foreign aid should sustain strong growth. The Bank of Mozambique (BM) will continue to target base money and facilitate absorption of the additional foreign aid while a strengthening of Public Financial Management (PFM) systems ensure a better monitoring of expenditures.